Giant oral lipoma: a rare entity - José Burgos Ponce; Gustavo Zanna Ferreira; Paulo Sérgio da Silva Santos; Vanessa Soares Lara (Sociedade Brasileira de Dermatologia, 2016)
Abstract Lipomas are very common benign slow-growing soft tissue neoplasms composed of mature adipose tissue mostly diagnosed in the fifth decade of life. These tumors rarely present in the oral cavity, representing less than approximately 5% of all benign mouth tumors. They are usually less than 2cm in size and etiology remains unclear. We report a young male patient presenting with a giant lipoma in the buccal mucosa. Histopathology revealed a large area of mature fat cells consistent with conventional lipoma and an area of the mucosal lining of the lesion suggestive of morsicatio buccarum. In the present article, we emphasize the clinicopathological features and differential diagnosis of the disease.